Fabrication and pilot-production of ultrahigh thermal conductivity vertical graphite-silicone pads with very low cost. (July 2022) - Tuersun, Yisimayili; Lin, Weiguang; Huang, Xu; Qiu, Wangkang; Luo, Pingjun; Huang, Mingdeng; Chu, Sheng
Abstract: Development of high thermal conductive silicone pads with mechanical softness as well as low cost have long been a challenge for effective thermal management in electronics. Here in this paper, we turn widely used commercial graphite sheet into small vertically aligned thermal conductive channel in gap filler pads. Laser process and vertical cutting techniques enable convenience vertical placement of tiny graphite flake into the silicone matrix. The composite thermal pad exhibit high through plane thermal conductivity of 296.24 W/mK, low thermal resistance of 0.19 cm 2  K/W and favorable mechanical characteristics. Thermal transportation simulation confirms the efficient heat channel formed by graphite flakes. For applications, CPU temperature can be lowered down by 3.1 °C in smartphone operation test compared with the original thermal pad, while the temperature at the back cover can also be brought down by 2.9 °C. Graphical abstract: Image 1 Highlights: High κ thermal pads were fabricated by simple and cost-effective way for meet the practical application requirement. Vertical alignment of graphite film in silicone matrix enables the thermal pad with continuous thermal conductive channel and favorable mechanical property. Excellent thermal conductivity, low thermal resistance and low compression moduloes (0.30 Mpa) provide multiple advantage for thermal dissipation.